Mengungkap Elemen Stilistik dalam Puisi-puisi Emily Dickinson Melalui Pendekatan Formalis - Juwintan, Juwintan; Hayati, Fadilla Putri (LITERATUS, 2024)
This study aims to analyze the stylistic elements in four poems of Emily Dickinson. Using a formalistic approach, this research focuses on three main aspects: semantic deviation, syntactic deviation, and discourse deviation, to reveal the distinctive style and profound meaning in the poems. This research uses a qualitative analysis method with a descriptive-analytic approach. Data collection was done by reading the five poems carefully using the close reading method. The analysis focused on identifying patterns of linguistic deviation and other textual elements that form Dickinson's stylistic characteristics. The results show that semantic deviations in Emily Dickinson's poems allow the poet to express abstract ideas, such as death, hope, and spirituality, through the use of metaphors, symbols, and personification. Syntactic deviations, such as inversions and the use of dashes, create unique rhythms and pauses, deepening the meaning and emotional atmosphere of the poems. Reflective and non-linear discourse structures, as well as imperfect rhyme patterns, provide a musical dimension that enriches the harmony between innovation and tradition in the poems. The findings suggest that the combination of such deviations not only enriches Dickinson's poetic style, but also reinforces universal themes such as life, death, and transcendence. This research confirms the importance of a formalistic approach in understanding how elements of language and formal structure contribute to the aesthetic appeal and deep meaning in her work